History and its use - Noyes, Susie Amanda (My University, 1893)
Introduction: Everything must have a beginning and profane history, like all other branches of learning began somewhere in the remote past, how and when we know but little. The earliest records are but chronicles of the bald facts. It is only recently that history has received any special attention. Modern history in Europe began with the romance. The earliest historical production in England, of which we have a record was in the form of a poem called “Layamon’s Brut.” This appeared about the year twelve hundred, and was a chronicle of British events from the time of the Roman invasion till the close of the seventh century. A little later about the time of the Norman Conquest, another historical record call the “Saxon Chronicle” was published. As history advanced still farther the writers strove to please the fancies and emotions.
Citation: Noyes, Susie Amanda. History and its use. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: History; Modern history; Europe; Norman conquest; Theses; Manuscripts (documents)